1998
DOI: 10.1074/jbc.273.20.12584
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-induced Apoptosis of A375 Human Melanoma Cells

Abstract: Endothelin-1 (ET-1) inhibited serum-dependent growth of asynchronized A375 human melanoma cells, and the growth inhibitory effect was markedly enhanced when ET-1 was applied to the cells synchronized at G 1 /S boundary by double thymidine blocks. Flow cytometric analysis revealed that ET-1 did not inhibit the cell cycle progression after the release of the block but caused a significant increase of the hypodiploid cell population that is characteristic of apoptotic cell death. ET-1-induced apoptosis was confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 35 publications
2
63
0
Order By: Relevance
“…In most cells, activation of ET A promotes cell growth , whereas activation of ET B induces cell death via apoptosis (Okazawa et al, 1998). In addition, binding of ET-1 to ET B results in clearance of ET-1 from the circulation.…”
mentioning
confidence: 99%
“…In most cells, activation of ET A promotes cell growth , whereas activation of ET B induces cell death via apoptosis (Okazawa et al, 1998). In addition, binding of ET-1 to ET B results in clearance of ET-1 from the circulation.…”
mentioning
confidence: 99%
“…A recent study showed that endothelin-1 induces apoptosis of human melanoma cells and inhibits their growth (Okazawa et al, 1998). This signal is mediated by endothelin (Okazawa et al, 1998). Hypermethylation of the 5' CGI of the ETRB gene and its decreased expression have been reported in human prostate cancers (Nelson et al, 1996(Nelson et al, , 1997.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelin-1 was originally identi®ed as a potent vasoconstrictive peptide (Yanagisawa et al, 1988), and subsequent studies revealed its diverse biological roles (Masaki et al, 1992). A recent study showed that endothelin-1 induces apoptosis of human melanoma cells and inhibits their growth (Okazawa et al, 1998). This signal is mediated by endothelin (Okazawa et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…As the ET-1 mRNA levels gradually decreased over 14 days postpartum, we also observed a gradual decrease in the thickness of the uterine wall, which was enlarged and thickened for pregnancy, particularly the myometrium (data not shown). It is well known that ET-1 has not only mitogenic activity but also an ability to induce apoptosis via the ETB receptor (Okazawa et al 1998). In vascular smooth muscle, it has been proposed that ET-1 caused apoptosis via the ETB receptor induced by stretch stimuli (Cattaruzza et al 2000).…”
Section: Discussionmentioning
confidence: 99%